2009
DOI: 10.1186/1757-1626-2-199
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of chelation therapy for the remission of symptoms caused by previous treatment with mercury-containing pharmaceuticals: a case report

Abstract: IntroductionA great deal of data regarding the toxicology of mercury has been recently reported. Although the most common human exposures to mercury are currently mercury vapour from amalgam tooth fillings, methylmercury from seafood and ethylmercury as a preservative in vaccines, in the past mercury compounds have been used in the treatment of syphilis.Case presentationMercury intoxication was found in a 67 year-old Italian man affected by neurological symptoms of apparently unknown origin. The patient develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In our experience, as shown in previous studies and in the present, removal of toxic metals has induced beneficial effects by improving patient symptoms [29, 33, 34]. No adverse effects were observed from EDTA treatments.…”
Section: Discussionsupporting
confidence: 81%
“…In our experience, as shown in previous studies and in the present, removal of toxic metals has induced beneficial effects by improving patient symptoms [29, 33, 34]. No adverse effects were observed from EDTA treatments.…”
Section: Discussionsupporting
confidence: 81%
“…However, the binding of chelating agent EDTA to toxic metals enabled the patient to progressively eliminate elevated urinary concentrations of aluminium, lead and mercury. EDTA performs stable complexes with metals in function of mass, pH and affinity (Corsello et al 2009). The tissue of origin of toxic metals before removal by EDTA is possibly the CNS, but also other tissues are involved.…”
Section: Discussionmentioning
confidence: 99%
“…In the specific case here described, the patient's detoxification from heavy metals seems to create the environmental conditions useful to improve the clinical signs of MS. We previously used the chelation therapy to cure a patient who was treated many years ago with mercury-containing pharmaceuticals and developed neurologic symptoms (Corsello et al 2009). It has been recently demonstrated that EDTA chelation therapy, without added vitamin C, decreased oxidative DNA damage and lipid peroxidation (Roussel et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the past we had already reported how mercury contained in drugs can be removed by EDTA chelation treatment (Corsello et al 2009). This study shows how the very same treatment can help remove toxic metals from a RA patient and how important oxidative status profile is in helping diagnose the stages of an autoimmune disease, such as RA.…”
Section: Discussionmentioning
confidence: 99%